2022
DOI: 10.4103/jfmpc.jfmpc_1177_21
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine pre-exposure prophylaxis for COVID-19 among healthcare workers: Initial experience from India

Abstract: Background: Hydroxychloroquine (HCQ) had generated considerable interest for coronavirus disease 2019 (COVID-19) prophylaxis. We conducted a prospective observational study at a tertiary care hospital in India, with dedicated COVID-19 care facilities. Objectives: Primary objective was incidence of adverse effects, secondary objective being efficacy in preventing COVID-19. Methods: Healthcare workers were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…Since HCQ has proven to be able to prevent SARS-CoV-2 infection in vitro,31 32 a number of clinical trials and observational studies embarked on evaluating HCQ as prophylaxis to contain SARS-CoV-2 in the human body. Most of these studies reported non-significant associations between HCQ prophylaxis and reduced SARS-CoV-2 infection rate,15 19 21 33–50 while only a few reported HCQ prophylaxis could significantly decrease SARS-CoV-2 infection rate 51–59. Our findings of significant association between PrEP use of HCQ and reduced risk of SARS-CoV-2 infection in clinical trials are consistent with another meta-analysis of cohort studies among high-risk HCWs performed by Stricker and Fesler 60.…”
Section: Discussionsupporting
confidence: 87%
“…Since HCQ has proven to be able to prevent SARS-CoV-2 infection in vitro,31 32 a number of clinical trials and observational studies embarked on evaluating HCQ as prophylaxis to contain SARS-CoV-2 in the human body. Most of these studies reported non-significant associations between HCQ prophylaxis and reduced SARS-CoV-2 infection rate,15 19 21 33–50 while only a few reported HCQ prophylaxis could significantly decrease SARS-CoV-2 infection rate 51–59. Our findings of significant association between PrEP use of HCQ and reduced risk of SARS-CoV-2 infection in clinical trials are consistent with another meta-analysis of cohort studies among high-risk HCWs performed by Stricker and Fesler 60.…”
Section: Discussionsupporting
confidence: 87%